2018
DOI: 10.17221/6/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin from slow-release implants on aquaporins (AQP1 and AQP4) in the ovine choroid plexus

Abstract: Szczepkowska A., Skowroński M.T., Kowalewska M., Milewski S., Skipor J. (2018): Effect of melatonin from slow-release implants on aquaporins (AQP1 and AQP4) in the ovine choroid plexus. Czech J. Anim. Sci., 63, 32-42.Aquaporins (AQPs) play important role in the cerebrospinal fluid (CSF) secretion and AQP1 and AQP4 are localized in the choroid plexus (CP), which is the main place of CSF production. In ewes, seasonally breeding animals, the turnover rate (TOR) of CSF is photoperiodically modulated and melatonin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Lp r is mainly regulated by aquaporin activity before the change of root morphology and structure, it plays a prominent role in plant response to short-term water deficiency stress [23]. It has been shown that MEL could significantly increase the mRNA expression level of aquaporin and the protein level of aquaporin isoforms in animals [24]. In addition, during the postharvest life in tomato, MEL treatment increased the expression of aquaporin genes with enhanced water loss in tomato fruit [25].…”
Section: Introductionmentioning
confidence: 99%
“…Lp r is mainly regulated by aquaporin activity before the change of root morphology and structure, it plays a prominent role in plant response to short-term water deficiency stress [23]. It has been shown that MEL could significantly increase the mRNA expression level of aquaporin and the protein level of aquaporin isoforms in animals [24]. In addition, during the postharvest life in tomato, MEL treatment increased the expression of aquaporin genes with enhanced water loss in tomato fruit [25].…”
Section: Introductionmentioning
confidence: 99%
“…In two of our previous studies, using a sheep model with melatonin implants (mimicking short days) and control animals (long days), we considered the effect of the photoperiod on ChP functioning. In this study, we used combinations of three reference genes: glyceralaldehyde-3-phosphate dehydrogenase (Gapdh), histone deacetylase 1 (Hdac1), and succinate dehydrogenase A (Sdha) [35], as well as a combination where Sdha was replaced by Actb [36]. This selection was based on our previous experience using the same sheep model, where we used Gapdh, Hdac1, and Actb [37,38].…”
Section: Discussionmentioning
confidence: 99%